Pembelajaran Berbasis E-Learning di Prodi Diploma III Kebidanan Perguruan Tinggi MH Thamrin - Surachman, Arie (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2024)
Infrastructure Support of Network of Computer in Study program of Diploma III of Midwifery of STIKes MH Thamrin very trigger to developing of facility of service to student. Besides Information System Akademik, hence the matter which have come to demand in lecturing is ready of medium learn to teach or the lecturing. Research into newest mention that student now claim the more amount time which with quality to be able to discuse and assist understanding in lecturing. Look in the face in class becoming not last for fulfilling time which with quality that. One of alternative is developing of system of e-learning which can give the more amount time and opportunity to student to be able to discuse. E-Learning is a process of study of where forwarding of items, discussion, and others activity of lecturing conducted by through electronic media. system of E-Learning developed is base on web and use moodle as software of its study, so that system of this e-learning is referred as by Internet Enabled Learning. Until so far system of e-learning developed in Study program of Diploma III of Midwifery of STIKes MH Thamrin have at phase of implementation and test-drive. System of E-Learning have in practice of at some lecturing activity, among other things the lecturing Draw Technique of at anomalous semester 2011/2012. From result of examination of System of E-Learning of at some eye kuliah, mean of responder interested and enthusiastic use model of this study. With exploiting of e-learning as medium of study expected by quality of study and result of learning expected will progressively the goodness. Result of some test- drive of study by e-learning that have given a lot of input for the system repair.